The fracture of two-layer leaf spring: Experiments and simulation. (March 2022) - Cheng, Guang; Chen, Kaiyuan; Zhang, Yu; Chen, Yuanchang
Highlights: Fatigue fracture that happened on a two-layer leaf spring with a decarbonization layer was reported, and fracture surface was carefully studied. 2-D and 3-D simulations illustrated the effect of the decarbonization layer and the fracture processing, respectively. 2-D simulation indicates the addition of cushion pads would be helpful to avoid failure. Abstract: Leaf spring is often used in commercial vehicles' suspension systems to ensure ride comfort and support dynamic wheel loads. In this study, we found a failure phenomenon in a two-layer leaf spring where the fatigue fracture occurred on the companion spring leaf. The decarbonization layer was observed on the surface of the leaf with a 100 μm thickness. The Vickers hardness of the leaf was reduced from ∼ 550 Hv of the inner material to ∼ 500 Hv at the surface region. The decarbonization layers led to fatigue fracture initiation, propagation, and total failure of the spring. Two-dimensional (2-D) finite element simulations were conducted to illustrate the effects of the decarbonization layer and the surface defects. Also, the fracture process was represented in the three-dimensional (3-D) simulation. We conclude that either additional surface treatments or installing rubber pads between each leaf will be helpful to raise the leaf spring's durability.